2017
DOI: 10.3233/ch-160219
|View full text |Cite
|
Sign up to set email alerts
|

Blood storage alters mechanical stress responses of erythrocytes

Abstract: BACKGROUND: Erythrocytes undergo irreversible morphological and biochemical changes during storage. Reduced levels of deformability have been reported for stored erythrocytes. Erythrocyte deformability is essential for healthy microcirculation.OBJECTIVE: The aim of this study is to evaluate shear stress (SS) induced improvements of erythrocyte deformability in stored blood.METHODS: Deformability changes were evaluated by applying physiological levels of SS (5 and 10 Pa) in metabolically depleted blood for 48 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
3
5
0
Order By: Relevance
“…Our results suggest that changes unfold in two phases bridged by a 2‐week plateau (between Days 7 and 21) when changes in RBC deformability are not statistically significant. Previous reports of deformability impairment occurring before Day 7 or after Day 21 are partly in line with our observations . Bennett‐Guerrero et al concluded that RBC deformability measured using ektacytometry was gradually altered over the 42‐day storage period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggest that changes unfold in two phases bridged by a 2‐week plateau (between Days 7 and 21) when changes in RBC deformability are not statistically significant. Previous reports of deformability impairment occurring before Day 7 or after Day 21 are partly in line with our observations . Bennett‐Guerrero et al concluded that RBC deformability measured using ektacytometry was gradually altered over the 42‐day storage period.…”
Section: Discussionsupporting
confidence: 92%
“…RBC deformability impairment has previously been reported as part of storage lesions, while the moment of occurrence is still a matter of debate . Our results suggest that changes unfold in two phases bridged by a 2‐week plateau (between Days 7 and 21) when changes in RBC deformability are not statistically significant.…”
Section: Discussionmentioning
confidence: 45%
“…These progressive morphologic and metabolic changes in RBCs after processing (washing alone or Percoll separation) and throughout storage were accompanied by changes in RBC quality characteristics including increased hemolysis and decreased Hb‐p50 and deformability, which is consistent with previously reported results 34,62–64 . The significantly increased hemolysis and rigidity and decreased elongation in the group of washed but unseparated RCCs show the high sensitivity of RBCs to the secondary effect of washing and storage methods on processed RBCs.…”
Section: Discussionsupporting
confidence: 90%
“…57,58 These progressive morphologic and metabolic changes in RBCs after processing (washing alone or Percoll separation) and throughout storage were accompanied by changes in RBC quality characteristics including increased hemolysis and decreased Hb-p50 and deformability, which is consistent with previously reported results. 34,[62][63][64] of senescent RBCs within a RCC will presumptively have higher accumulation of side products of aging/lysis that undoubtedly affect the quality of the whole RCC unit. Other studies have discussed the impact of donor age and sex on both the quality characteristics of RCCs during in vitro storage 22,25,28,65 and the transfusion efficacy, [66][67][68][69] with an increased risk of mortality due to sex-mismatched transfusions.…”
Section: Intracellular Reactive Oxygen Species and Ca 2+ In Rbcs Dumentioning
confidence: 99%
“…Blood coagulation and fibrinolysis are complex processes in which platelets, fibrins, enzymes, and a series of complex chemical reactions play a role. Since red blood cells (RBCs) also have significant functions in blood clotting and its disorders (Demiroglu, 1997;Yalcin et al, 2016;Litvinov and Weisel, 2017), the RBC rheology in different disease conditions has been widely studied (Ertan et al, 2017;Ugurel et al, 2017;Yalcin et al, 2017). For example, red blood deformability is controlled by calcium (Yalcin et al, 2016) and it directly affects the blood viscosity and clotting.…”
Section: Introductionmentioning
confidence: 99%